2002
DOI: 10.1038/sj.jhh.1001482
|View full text |Cite
|
Sign up to set email alerts
|

Association between the blood pressure response to a change in posture and the 6-year incidence of hypertension: prospective findings from the ARIC study

Abstract: The association between the blood pressure response to a change from the supine to the standing position and the 6-year incidence of hypertension was studied in a biethnic, middle-aged cohort of 6951 normotensive men and women free of coronary heart disease at baseline. Postural change in systolic blood pressure (SBP) was categorized into deciles, and the middle four deciles served as the referent (no change) group. In unadjusted analyses, the incidence of hypertension was higher among both those with SBP incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
3
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 32 publications
4
51
3
5
Order By: Relevance
“…This approach thus overcomes some of the problems caused by the multicollinearity of study data that are inherent in epidemiological studies focusing on traditional measures of BP and BP during challenge. For example, in a study by Rose et al, 8 adjusting for baseline BP attenuated the association between future incident hypertension and both positive and negative BP reactivity to postural challenge. It is possible that Rose et al's findings may be owing to an overadjustment for baseline BP.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This approach thus overcomes some of the problems caused by the multicollinearity of study data that are inherent in epidemiological studies focusing on traditional measures of BP and BP during challenge. For example, in a study by Rose et al, 8 adjusting for baseline BP attenuated the association between future incident hypertension and both positive and negative BP reactivity to postural challenge. It is possible that Rose et al's findings may be owing to an overadjustment for baseline BP.…”
Section: Discussionmentioning
confidence: 98%
“…These findings contradict some studies examining BP response to postural change. For example, some studies have found that DSBP to postural change (standing) is influenced by cigarette smoking, 3,5 certain antihypertensive medication 8,43 and BMI. 3,5,8 However, other studies indicate that BP response to postural change is not influenced by cigarette smoking, 8,13,43 hypertensive medication 3,5 or BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OH has been shown to occur well in advance of CVD, even preceding some CVD risk factors, such as hypertension 39. Furthermore, sudden recurrent decreases in BP with standing could contribute to end‐organ damage.…”
Section: Discussionmentioning
confidence: 99%